Evaluation of garlic (Allium sativum) varieties for better growth and yield for Madhya Pradesh (Current Horticulture, 2024)
Garlic (Allium sativum L.) is grown as a winter crop in Madhya Pradesh, Gujarat, Rajasthan, Maharashtra and Uttar Pradesh. Madhya Pradesh is the largest producer of garlic in India, occupying 81.17 thousand ha with a total production of 424.50 thousand tonnes. In India, garlic is cultivated in 134.9 thousand hectare. Lack of high-yielding varieties is one of the main constraints in limiting the production and productivity. Keeping in view, Krishi Vigyan Kendra, Burhanpur, conducted on-farm trial to assess the performance of different varieties in Nimar region: a) to identify high-yielding and environmentally suitable varieties/cultivars and b) to test their suitability and productivity.